2017
DOI: 10.17851/2237-2083.25.4.2293-2327
|View full text |Cite
|
Sign up to set email alerts
|

Organização retórica do resumo acadêmico gráfico: um gênero acadêmico multimodal

Abstract: Resumo: Este artigo relata a investigação do resumo acadêmico gráfico (RAG), prática discursiva multimodal típica de certas áreas do contexto acadêmico. Metodologicamente, empregou-se a Análise Crítica de Gênero (MEURER, 2002; BHATIA, 2004; MOTTA-ROTH, 2006, 2008) a fim de analisar as características textuais e contextuais de 40 RAGs de Química e de Biologia e descrever sua organização retórica prototípica. Para a análise textual, efetuaram-se: i) identificação, descrição e categorização dos significados dos m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Web-native GAs have little more than a decade of life and, in terms of studies explicitly oriented to the analysis of the rhetorical moves of this part-genre, there seems to be no conclusive evidence about the predominant organization pattern. However, the works of Sancho Guinda (2015), Yoon and Chung (2017), and the doctoral research of Florek (2018) have provided insightful directions on the topic.…”
Section: Move Structure Of Gas: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Web-native GAs have little more than a decade of life and, in terms of studies explicitly oriented to the analysis of the rhetorical moves of this part-genre, there seems to be no conclusive evidence about the predominant organization pattern. However, the works of Sancho Guinda (2015), Yoon and Chung (2017), and the doctoral research of Florek (2018) have provided insightful directions on the topic.…”
Section: Move Structure Of Gas: Previous Studiesmentioning
confidence: 99%
“…Finally, in a study of 30 GAs in the fields of chemistry, engineering, and related interdisciplinary areas, Florek (2018) identified that Results and Methods were Vol. 11(2)(2023): 237-260 obligatory moves, present in all the GAs.…”
Section: Move Structure Of Gas: Previous Studiesmentioning
confidence: 99%